Formulation of fenofibrate nanocrystals with wet milling method - M. Henityo Agung As'adi; Ilham Kuncahyo; Teuku Nanda Saifullah Sulaiman (Riset Informasi Kesehatan, 2023)
Background: Fenofibrate is an antihyperlipidemic belonging to BCS class II, practically insoluble in water and has high lipophilicity, so it is proven that the inhibitor of the rate of absorption of fenofibrate from the digestive tract is slow to dissolve. This study aims to increase the solubility of fenofibrate by forming nanocrystals. Method: Formation of nanocrystals using the wet milling method Result: The fenofibrate nanocrystals produced a particle size of 775.966 nm, a zeta potential of -21.302 mV, and a solubility of 5.977 Î¼g/mL. Conclusion : The optimum formula with tween 80 components, grinding speed and grinding time in the manufacture of fenofibrate nanocrystals using the Factorial Design method obtained 0.2% tween 80, grinding speed of 500 rpm and grinding time of 1 hour. The critical parameter test results for the optimum formula obtained a particle size of 775.966 nm, a zeta potential of -21.302 mV and a solubility of 5.977 Âµg/mL. The DSC test showed that there was a difference in the melting point peaks and a decrease in crystal intensity between pure fenofibrate and fenofibrate nanocrystals. The FTIR test showed no difference in functional groups between pure fenofibrate and fenofibrate nanocrystals. The XRD test showed that there was a difference in peak crystal intensity between pure fenofibrate and fenofibrate nanocrystals. The SEM analysis shows that there are differences in shape and magnification used between pure fenofibrate and fenofibrate nanocrystals.